Eigenarten, Beharrungskräfte und Widersprüche im föderalismustheoretischen Diskurs der Bundesrepublik. - Scheller, Henrik (Berliner Wissenschafts-Verlag, 2021)
The assumptions that underlie the repertoire of relevant theoretical concepts of federalism in the German debate are made only rarely explicitly and reflected critically. That implies the risk ofa further decoupling ofthe academic from the political discourse. In addition, practical reform proposals are increasingly overburdened by a (tacit) equating of the democracy and the federalism principle. To address this dilemma, it needs again a broader debate about axiomatic conflict of goals.
Peculiarities, inertia forces and contradictions in the discourse on federalism theory of the Federal Republic.
Keywords: Föderalismus; Demokratie; Föderalismustheorie; Demokratietheorie